Simultaneous test to aluminum tolerance and giberelic acid sensibility in hexaploid wheat - Dornelles, Ana Lúcia Cunha; Carvalho, Fernando Irajá Félix de; Federizzi, Luiz Carlos; Sereno, Maria Jane Cruz de Melo; Amaral, Adriane; Mittelmann, Andréa (Pesquisa Agropecuaria Brasileira, 1997)
In nutritive solution, six genotypes of hexaploid wheat, with known behavior in aluminum (Al) tolerance and giberellic acid (GA3) sensibility, were tested. Two Al concentrations (zero and ten ppm) and three times of GA3 introduction (no GA3, GA3 at the fifth day and GA3 at the eight day of experiment) were studied in a 2 x 3 fatorial design. The results showed that this kind of simultaneous test is efficient, and that there is no interaction between these two factors. The treatments that best fitted to the waited genotypes behavior were those with ten ppm of Al and GA3 introduction at the eighth day of experiment.